2020
DOI: 10.1002/adem.202000758
|View full text |Cite
|
Sign up to set email alerts
|

Screw Pump‐Type Water Triboelectric Nanogenerator for Active Water Flow Control

Abstract: Triboelectric nanogenerators (TENGs) have been spotlighted due to the high efficiency, low cost, and easy accessibility. Despite their advantage, TENGs exhibit certain limitations such as a low lifetime. To overcome the limitation, the use of water–solid contact TENGs has been suggested. Most of the studies about water–solid contact TENG are focused on optimizing the device to adjust to the stagnant water or natural water movement. However, in most actual fluid machinery applications, the flow of water can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Angular speed and water volume ratio are also factors affecting the closed system with a rotating structure. [ 18,33a,33c,35,38,86 ] As shown in Figure 12c, keeping a certain volume of water, the electric output performance of TENG first increases and then decreases with the increase of speed (the maximum electric output corresponds to a speed of 200 rpm) [10b] . Additionally, the electric output of the TENG increases with the volume ratio of water at a low angular speed (<150 rpm).…”
Section: The Influence Of Structural Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Angular speed and water volume ratio are also factors affecting the closed system with a rotating structure. [ 18,33a,33c,35,38,86 ] As shown in Figure 12c, keeping a certain volume of water, the electric output performance of TENG first increases and then decreases with the increase of speed (the maximum electric output corresponds to a speed of 200 rpm) [10b] . Additionally, the electric output of the TENG increases with the volume ratio of water at a low angular speed (<150 rpm).…”
Section: The Influence Of Structural Factorsmentioning
confidence: 95%
“…Furthermore, the influence of humidity can be mostly ignored, especially when water is used. [ 17 ] Apart from that, there are many different types of liquid, such as water, [ 18 ] different solutions, [ 19 ] oils, [ 20 ] and some liquid metals, which provide a huge potential for various designs and applications. In comparison with other energy systems, such as electromagnetic generators [ 21 ] and some liquid batteries, [ 22 ] the liquid‐interfaces‐based TENG (LI‐TENG) offers a wide range of materials that can be chosen to realize the fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…TENG has the potential to be an alternative energy source with various advantages such as low cost, simple design, and high applicability. Owing to its advantages, various studies have been reported on the practical applications of TENG [10][11][12]. Notably, several researchers reported wearable TENG devices that can power electronics by human movement [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…When multiple devices are combined, electric signals of a wide frequency range and high outputs can be achieved compared with when a single device is used [ 15 , 16 , 17 , 18 , 19 ]. Finally, by using wind power, the direction of the wind can be detected [ 20 , 21 , 22 , 23 ] and the amount of rainfall can be measured [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%